Ecological aspects of catholic moral theology - Ciszek, Mariusz (Studia Ecologiae et Bioethicae, 2004)
The ecological aspect of catholic moral theology should not evoke astonishment, as it is not a strange hybrid created by means of artificial manipulations aiming at bestowing authority of Christian tradition on ecology. Popes' statements concerning natural environment conservation seem to testify against such claims and only show the importance and need of implementing responsible and moderate using the Earth's resources into Christian awareness. Practical ethical problems in the ecological aspect I started to present from the natural law, which determines divine moral order in the world, also in the ecological dimension. Then I undertook the problem of an ecological conscience, which is a kind of a "watchman" of our morality, also as far as human actions in the natural environment are concerned, and it tries to protect the human being from committing an ecological sin, which is one of the forms of disobedience to God. These ecological aspects of moral theology will remain just hot air if we do not spread them by means of ecological education. It is also very important to shape proper and fixed attitudes towards other people and nature that can be described in terms of love, prudence, and moderation as aretology (field of science concerning virtues) teach us. At the end of this paragraph, I put Ecological Decalogue, whose rules Christians should obey in everyday life.